Risk factors, complications and management of lymphocele formation after radical prostatectomy: A mini‐review. (2nd April 2019) - Tsaur, Igor; Thomas, Christian
Abstract: Lymphocele formation is the most common adverse event of pelvic lymphadenectomy during radical prostatectomy for prostate cancer. Previous studies failed to favor one surgical technique over the other in terms of minimizing its rate. Data on risk factors for its development are still conflicting and warranting further research. In this mini‐review, we aimed to scrutinize available evidence on these aspects and outline current achievements in lymphocele prevention approaches.